The feasibility of kaolin as main material for low cost porous ceramic hollow fibre membrane prepared using combined phase inversion and sintering technique - Hubadillah, Siti Khadijah (Penerbit UTM Press, 2017)
Ceramic hollow fibre membrane (CHFM) demonstrated superior characteristics and performance in any separation application. The only problem associated with this kind of technology is the high cost. In order to effectively fabricate and produce low cost porous CHFM, a series of CHFMs made of kaolin were fabricated via combined phase inversion and sintering technique. The CHFMs from kaolin named as kaolin hollow fibre membranes (KHFMs) were studied at different kaolin contents of 35 wt.%, 37.5 wt.% and 40 wt.% sintered at 1200ºC. The result indicated that by varying kaolin contents, different morphologies were obtained due to changes in the viscosity of ceramic suspension containing kaolin. The optimum kaolin content for KHFM was identified. It was found that KHFM prepared at 37.5 wt% has a mechanical strength and pure water flux of A and B respectively.